Gambaran Pertandingan Cabang Olahraga Muaythai Kelas Wai Khru Putra dan Putri pada PON XX 2021 Papua - Novita Anggi Ayuni; Heri Wahyudi (Jurusan Pendidikan Kesehatan dan Rekreasi, 2021)
Background: Muaythai is a martial art originating from Thailand, muaythai was first known in Indonesia in 2013 with a parent organization called the Indonesian Muaythai Executive Board (PBMI). In the Muaythai sport, there are various categories that are competed, namely the category of fighting (fight) and the arts (Wai Khru). Muay Thai is a tactic and sport that is a cultural heritage of Thai-style martial arts that has been passed down from ancestors for a long time as a weapon to protect the land from other countries. and women at the XX PON in Papua, so that the results of the research can be used as evaluation material for coaches and athletes in developing and improving athlete achievement. Methods: The research method is used to achieve or not a research. In this study using a qualitative research type, the source of data taken for this research sample amounted to 19 athletes consisting of 11 male athletes and 8 female athletes in the Wai Khru class. Results: Muhammad Uchida from DKI Jakarta, Muhammad Zull Alidja from Papua won 2nd place and joint 3rd place was won by Abdul Rozak from South Kalimantan and Aldento Brilliana Bara from East Java. And the winner in the women's Wai Khru class won 1st place by Tiara Laili.K.M from Papua, 2nd place went to Luh Mas Sri.D.W from Bali, and joint 3rd place went to Nadia Indah.R from South Sulawesi and Novita Anggi Ayuni from Bengkulu. In this Wai Khru class competition, the assessments taken include the neatness and beauty of the costume (dress), the beauty of the basic movement (basic performance smooth), the beauty of the movement accompanied by music (each performance follow thru music and smooth), flexibility and strength (flexibility and strength). strong), and the duration of time (time) with the duration of the demonstration not more than 5 minutes. Conclusions: Based on the above research, it can be concluded that the Muaythai sport originated from Thailand which later developed in Indonesia under the PBMI federation (Indonesian Muaythai Executive Board), Muaythai consists of two categories, namely the Tanding category and the Wai Khru Arts category. In this article, research is conducted on the evaluation results of the Wai Khru class Muaythai sports competition at the XX PON 2021 in Papua, which amounted to 19 male and female athletes from a total of 129 athletes, there were four athletes who won the title in each category starting from the matches in the male and female Wai Khru classes are taken based on the assessment of each match judge and all results are collected to find the best score or score.